Pengaruh konsentrasi larutan kapur sebagai curing terhadap kualitas fisiko-kimia dan organoleptik gelatin kulit kambing Peranakan Ettawah (PE) - Amertaningtyas, Dedes; Thohari, Imam; Purwadi, Purwadi; Radiati, Lilik Eka; Rosyidi, Djalal; Jaya, Firman (Faculty of Animal Science, Universitas Brawijaya, 2014)
The purpose of this study was to determine effect of lime concentration in the gelatin manufacture from goat skins in terms of physico-chemical and to determine the best lime concentration that can be used for gelatin manufacture from goat skin. The materials used were 5 sheets of Ettawah crossbred goat skin aged 1.5-5 years and lime (Ca(OH)2). The results showed that different lime concentration in the curing process during the manufacture of goat skin gelatin had no effect (P>0.05) on the yield, viscosity, pH, water content, protein content and fat content. The best treatment was the use of 5% of lime concentration which resulted 12.82% of yield, 3.67 cP of viscosity, 2.7 of pH, 9.29% of water content, 73.58% of protein content and 1.77% of fat content. Keywords: Gelatin, goat skin